The relationship between Molecular Biology and Diagnostic Techniques for Sickle Cell Anemia (Research, Society and Development, 2024)
Sickle cell anemia is the most common monogenic hereditary disease in the world, causing a change in the shape of red blood cells, making them resemble a sickle. This alteration makes red blood cells less capable of transporting oxygen throughout the body and increases the risk of blood vessel obstruction. Mutations in the hemoglobin (Hb) gene are frequently found, and population migrations have contributed to their presence in most countries. According to the Globin Gene Server, 1,327 hemoglobin variants have been described across various racial, and ethnic groups, most of which do not have any clinical consequences. However, when combined, these variants can present relevant pathophysiology. This study aims to describe sickle cell anemia and the importance of its diagnosis. This is a descriptive and informative literature review, with all information drawn from recently published scientific articles, providing updated and well-established content. We hope this research will enrich our academic and scientific knowledge on the subject, and provide relevant information regarding the importance of understanding sickle cell anemia and its diagnosis.